Integration of constraint programming, artificial intelligence, and operations research : 15th International Conference, CPAIOR 2018, Delft, The Netherlands, June 26-29, 2018, Proceedings /: 15th International Conference, CPAIOR 2018, Delft, The Netherlands, June 26-29, 2018, Proceedings. (2018) - Unknown
No abstract available